2007
DOI: 10.1128/aem.01620-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microbial Immigration in the Colonization of Apple Leaves by Aureobasidium pullulans

Abstract: The role of microbial immigration in the veinal colonization pattern of Aureobasidium pullulans on the adaxial surface of apple leaves was investigated in two experiments at two periods (early and late seasons) in 2004 by applying green fluorescent protein (GFP)-tagged blastospores to the foliage of orchard trees. Individual leaves were resampled by a semidestructive method immediately after inoculation (t 0 ) and about 1 (t 1 ), 2 (t 2 ), and 3 (t 3 ) weeks later. At t 0 , there were no significant (P < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…On the basis of the above findings, it can be concluded that A. pullulans showed the largest spectrum of activities of all the species tested. This black yeast has been considered a major phylloplane yeast and has been found to occupy a specific leaf microhabitat with particular nutrient exudates . Therefore, its ubiquity and massive occurrence in the phylloplane can be explained by its ability to utilize various compounds present in different microhabitats.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the above findings, it can be concluded that A. pullulans showed the largest spectrum of activities of all the species tested. This black yeast has been considered a major phylloplane yeast and has been found to occupy a specific leaf microhabitat with particular nutrient exudates . Therefore, its ubiquity and massive occurrence in the phylloplane can be explained by its ability to utilize various compounds present in different microhabitats.…”
Section: Discussionmentioning
confidence: 99%
“…A group of researchers have tested the optimum pH for many samples and reprted that for all samples to be 7-7.5 depending on species, with maximum activity at pH 7.2. It has been shown that protease activity in Bacillus clausii [30] is higher than As pergillus nigar [25], Bacillus clausii [29], Aureobasidium pullulans [ 35], Bacillus alveayuensis [36], and Bacillus cereus [4]. These results indicated that for the growth of protease producing bacteria and fungi, alkaline environment is more suitable.…”
Section: Have Reported Twomentioning
confidence: 99%
“…it is pleomorphic) and lives in a wide variety of habitats is Aureobasidium pullulans. This fungus has been recovered from diverse surfaces types, especially the phylloplane (Andrews et al 2002, McGrath and Andrews 2007, Andrews and Harris 1997, Woody et al 2007. Examples of other surface sources include glass (Schabereiter-Gurtner et al 2001), painted material (Shirakawa et al 2002), as well as rocks and marble (Urzì et al 1999(Urzì et al , 2001.…”
Section: Introductionmentioning
confidence: 97%